DEPICTION OF FOLK DANCE IN HINDI NOVELS - Gupta, Neha (International Journal of Research -GRANTHAALAYAH, 2026)
In Indian culture, folk art holds a unique identity, with music, drama, and dance occupying a special place. Folk dance represents the cultural expression of rural life in India and is deeply connected with traditions, festivals, celebrations, and social sentiments. Hindi novels, which serve as a literary mirror of Indian society and culture, portray folk dance not only for aesthetic enrichment but also as a medium conveying social, cultural, and psychological meanings. Folk dances are not merely performances of movement and attraction; they symbolize community identity, social relationships, customs, and religious beliefs. When these dances are described in Hindi novels, authors present not only their technical structure but also their broader social and cultural significance to the reader. Through such depictions, literature preserves and interprets the living traditions of Indian folk culture.